2021
DOI: 10.1002/tox.23163
|View full text |Cite
|
Sign up to set email alerts
|

HBCD, TBECH, and BTBPE exhibit cytotoxic effects in human vascular endothelial cells by regulating mitochondria function and ROS production

Abstract: Brominated flame retardants (BFRs), such as, 1,2,5,6-tetrabromocyclooctane (HBCD), 1,2-dibromo-4-(1,2-dibromopropyl)cyclohexane (TBECH), and 1 1,2-bis-(2,4,6-tribromophenoxy)ethane (BTBPE), have garnered increasing attention due to their potent biological effects. In the present study, the toxicity of HBCD, TBECH, and BTBPE in human vascular endothelial cells (ECs) was explored. The data showed that HBCD, TBECH, and BTBPE induced cytotoxicity, namely dose-dependent cell viability reduction, cell membrane perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Additionally, acrolein could cause cell toxicity in HUVECs through regulating cell apoptosis, DNA damage response, and oxidative stress 35 . It was proved that brominated flame retardants induced call damage of HUVECs via modulating ROS production and mitochondria function 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, acrolein could cause cell toxicity in HUVECs through regulating cell apoptosis, DNA damage response, and oxidative stress 35 . It was proved that brominated flame retardants induced call damage of HUVECs via modulating ROS production and mitochondria function 36 …”
Section: Discussionmentioning
confidence: 99%
“…35 It was proved that brominated flame retardants induced call damage of HUVECs via modulating ROS production and mitochondria function. 36 ASV has extensive activities on the hematopoietic system, liver, endocrine system, nervous system, collagen metabolism, cardiac function, and organ immune system. 37 For example, ASV showed the inhibition influence on anti-apoptotic signaling and enhancement on apoptosis in hepatocellular carcinoma.…”
Section: Asv Treatment Assuaged Ox-ldl-induced Injury In Huvecs By Ta...mentioning
confidence: 99%
“…BTBPE is one of the most commonly used novel BFRs, applied especially in all these plastics, where PBDEs were previously used. Similar to HBCD and TBCO, BTBPE exhibits cytotoxicity and can damage plasma membranes . TBP is produced in quantities of 10 to 100 tons yearly and applied as novel BFR in some plastics .…”
Section: Methodsmentioning
confidence: 99%
“…Similar to HBCD and TBCO, BTBPE exhibits cytotoxicity and can damage plasma membranes. 47 TBP is produced in quantities of 10 to 100 tons yearly and applied as novel BFR in some plastics. 45 Moreover, TBP is a BFR of special environmental concern, as it is also a degradation product of multiple other BFRs, to name only PBDEs or BTBPE.…”
Section: Methodsmentioning
confidence: 99%
“…Also, HBCD has been detected in arctic regions [ 7 ] and breast milk [ 8 ]. There is global concern about the potential toxic effects of HBCD on humans and ecosystems [ 3 , 9 ] because of its persistence in the environment, bioaccumulation, and bioamplification in fish [ 10 ], birds [ 11 ], and mammals [ 12 , 13 ]. Recently many studies in animals have shown that HBCD can affect the expression of related genes in rats [ 14 ] and zebrafish [ 10 ].…”
Section: Introductionmentioning
confidence: 99%